2014
DOI: 10.1128/aac.02301-13
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole Therapy Protects Immunosuppressed Mice from Mucormycosis

Abstract: We studied the in vitro and in vivo efficacies of the investigational drug isavuconazole against mucormycosis due to Rhizopus delemar. Isavuconazole was effective, with MIC and minimal fungicidal concentration (MFC) values ranging between 0.125 and 1.00 g/ml. A high dose of isavuconazole prolonged the survival time and lowered the tissue fungal burden of cyclophosphamide/cortisone acetate-treated mice infected with R. delemar and was as effective as a high-dose liposomal amphotericin B treatment. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 33 publications
6
33
0
2
Order By: Relevance
“…An analytical method that uses ultraperformance liquid chromatography and single-quad mass spectrometry (UPLC/MS) for the determination of itraconazole and hydroxylitraconazole was adapted and validated for the measurement of ISA and POS (20,22), while high-performance liquid chromatography (HPLC) was used to measure VOR levels. All three drugs demonstrated serum drug levels in excess of MIC values (defined as the lowest drug concentration that causes 100% growth inhibition) against R. delemar 99-880 (MIC values of 0.5, 0.78, and 8.0 g/ml for ISA, POS, and VOR, respectively [17,23]) (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An analytical method that uses ultraperformance liquid chromatography and single-quad mass spectrometry (UPLC/MS) for the determination of itraconazole and hydroxylitraconazole was adapted and validated for the measurement of ISA and POS (20,22), while high-performance liquid chromatography (HPLC) was used to measure VOR levels. All three drugs demonstrated serum drug levels in excess of MIC values (defined as the lowest drug concentration that causes 100% growth inhibition) against R. delemar 99-880 (MIC values of 0.5, 0.78, and 8.0 g/ml for ISA, POS, and VOR, respectively [17,23]) (Fig. 1A).…”
mentioning
confidence: 99%
“…We have demonstrated the efficacy of ISA in treating mice infected with Rhizopus delemar (17). Hence, we wanted to assess the prophylactic activity of ISA compared to POS and VOR in protecting neutropenic mice from pulmonary mucormycosis.…”
mentioning
confidence: 99%
“…The results of in vitro and animal model studies have shown that isavuconazole is active against Candida spp. (both fluconazole-sensitive and fluconazole-resistant strains), Aspergillus spp., Cryptococcus spp., and other molds, including the Mucorales and Scedosporium species (21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Las equinocandinas no tienen actividad in vitro contra los mucorales; sin embargo, los estudios tradicionales de susceptibilidad podrían no reflejar la verdadera actividad de las equinocandinas contra los hongos filamentosos en general y contra los agentes productores de mucormicosis en particular. Existen reportes de que R. oryzae, el principal agente etiológico de mucormicosis, es capaz de expresar el blanco de acción de las equinocandinas; la 1,3 β-D glucano sintetasa; codificado por el gen FKS y que caspofungina inhibiría la actividad de la enzima in vitro y tendría actividad in vivo en modelos murinos diabéticos de mucormicosis diseminada 22,23 . Existen dos posibles mecanismos que explicarían por qué la adición de una equinocandina podría mejorar la eficacia del tratamiento con AmB en la mucormicosis: por disrupción de los enlaces β-glucano de la pared celular permitiendo una mayor llegada de AmB a la membrana celular, y por alteración de la virulencia del hongo retrasando la filamentación o alterando el contenido de la pared celular 22 .…”
Section: Mucormicosis Rino-cerebralunclassified
“…Existen dos posibles mecanismos que explicarían por qué la adición de una equinocandina podría mejorar la eficacia del tratamiento con AmB en la mucormicosis: por disrupción de los enlaces β-glucano de la pared celular permitiendo una mayor llegada de AmB a la membrana celular, y por alteración de la virulencia del hongo retrasando la filamentación o alterando el contenido de la pared celular 22 . La asociación de caspofungina con AmB en complejo lipídico ha mostrado sinergia in vitro y eficacia en los mismos modelos murinos 22,23 . En adultos se ha podido comprobar que pacientes tratados con la combinación polieno-caspofungina tienen una mejor sobrevida a los 30 www.sochinf.cl días del alta y a largo plazo.…”
Section: Mucormicosis Rino-cerebralunclassified